Implementation of Limitation of Prosecution of Land Rights to Ensure Legal Certainty for Rightsholders - Agus Yulianto (Unnes Law Journal, 2019)
Article 32 paragraph (2) Regulation 24 of 1997 states that the issue of land cases more than 5 years after the certificate is issued is not possible lawsuit. This is intended to ensure legal certainty for rights holders. But in reality, there is a problem a lot of land that is more than 5 years can still be carried out a lawsuit by those who feel harmed, so it does not ensure legal certainty for rights holders. This is possible because the system is a system used publications negative positive element in which the certificate is not as absolute proof, so that those who feel aggrieved can still raise objections without time limit. Results from this study is the case of land dispute resolution that appeared more than five years after the certificate issued is the same as the settlement of land issues that arose before 5 years after the certificate was issued. The solution can be done through litigation and non-litigation either at Court or the Land Office. Namely through the path of litigation proceedings from the lawsuit, the answer, replic, closing argument, evidence, conclusions, and judgment. While the path is non-litigation mediation can be done in the Courts and the Land Office. Restrictions prosecution land rights can ensure legal certainty of land rights holders. Because the landowners will not always alarmed by the continuity of the ownership of the land.